Evaluación de la expresión de subunidades recombinantes del receptor NMDA en la línea celular HEK-293. (2023)
The NMDA (N-methyl-D-aspartate) receptor plays a crucial role in synaptic function and neuronal plasticity, but its hyperactivation can lead to excitotoxicity, a phenomenon implicated in several neurodegenerative diseases. In this context, the use of peptides derived from animal toxins has emerged as a promising strategy to selectively modulate NMDA receptor activity and counteract excitotoxicity. These peptides, from diverse sources such as snakes and spiders, act as specific ligands of the NMDA receptor and can function as agonists, antagonists or allosteric modulators, interacting with different binding sites on the receptor.